New Natural History : Catalogue of the Exhibition - Williams, Val; Hobson, Greg; National Museum of Photography Film & Television, Bradford; Hasselblad Center, Gothenburg (Bradford : National Museum of Photography, Film & Television, 1999)
Arnatt, Keith ; Baker, Carole ; Ballen, Roger ; Toscani Ballo, Marirosa ; Barnes, Rosie ; Burkhard, Balthasar ; Chalmers, Catherine ; Dera, Cor ; Dion, Mark ; Fox, Anna ; et al.
National Museum of Photography, Film & Television, Bradford, 17 September - 14 November 1999 ; Hasselblad Center, Gothenburg, 22 January - 27 February 2000
kunstcatalogus